2015
DOI: 10.1302/0301-620x.97b3.35738
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of health-related quality of life in a United Kingdom hip fracture population

Abstract: Hip fracture is a global public health problem. The National Hip Fracture Database provides a framework for service evaluation in this group of patients in the United Kingdom, but does not collect patient-reported outcome data and is unable to provide meaningful data about the recovery of quality of life. We report one-year patient-reported outcomes of a prospective cohort of patients treated at a single major trauma centre in the United Kingdom who sustained a hip fracture between January 2012 and March 2014.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
122
2
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(140 citation statements)
references
References 15 publications
8
122
2
8
Order By: Relevance
“…In Swedish and Japanese studies, the proportion of surviving patients walking was found to be similar at 4 months and 1 to 2 years [31, 34, 45] and in community living people the proportion of survivors walking remained relatively constant to 10 years [31]. In contrast, a UK study found some increase in the proportion walking at 1 year [46]. …”
Section: Resultsmentioning
confidence: 99%
“…In Swedish and Japanese studies, the proportion of surviving patients walking was found to be similar at 4 months and 1 to 2 years [31, 34, 45] and in community living people the proportion of survivors walking remained relatively constant to 10 years [31]. In contrast, a UK study found some increase in the proportion walking at 1 year [46]. …”
Section: Resultsmentioning
confidence: 99%
“…The current annual hospital cost of hip fractures in the UK has been estimated at £1.1 billion (Leal et al, 2016). Thus, it is vital to further improve fracture prevention strategies, not only to decrease health care costs, but also to reduce devastating outcomes such as morbidity, disability, dependency, and poor quality of life (Griffin et al, 2015;Parker, 2016). Many, often modifiable, risk factors need to be considered for hip fracture prevention.…”
mentioning
confidence: 99%
“…While overall health indicators such as the EQ-5D have been accepted as reasonable compromises in that they can capture an adequate amount of information on these sometimes parlous health states and have adequate validity when completed by relatives or carers [13], the ultimate question in hip fracture care is whether we are restoring pre-injury function to these patients. This has been qualitatively demonstrated to be patients' greatest concern when considering hip fracture [14] and clear effects have been shown in recent output from the Warwick Hip Trauma Evaluation (WHiTE) study [15,16]. As this data is sourced locally rather than from national datasets, there is a possibility that patients who have experienced complications from their surgery have presented elsewhere and this episode has not been captured.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been demonstrated that these patients lose a significant quality of life permanently and, early in their recovery, a proportion rate their state of health as worse than being dead [3]. While care has advanced substantially in recent years, there remains a significant burden of mortality associated with the injury [4].…”
Section: Introductionmentioning
confidence: 99%